The influence of technological parameters of fermentation on functional peculiarities of cultured butter - Musiy, Lyudmila; Tsisaryk, Оksana; Slyvkа, Іrina; Galenko, Oleg (My University, 2016)
The determining factors of cultured butter production is fermentation processes (selection starting cultures, their relations and determinations of optimal technological parameters of fermentation) and physical cream maturation. Визначальними чинниками виготовлення кисловершкового масла є процеси ферментації (підбір заквашувальних культур, їх співвідношення та визначення оптимальних технологічних параметрів ферментації) та фізичного визрівання вершків.
Keywords: кафедра технології м’яса і м’ясних продуктів; вершки ферментовані; fermented cream; sour milk butter; вершкове масло кисловершкове